PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF - Lhony Laisnima; Zulfiani Zulfiani (Arfak Chem: Chemistry Education Journal, 2021)
Abstract The used of the jigsaw-type cooperative learning model can improve the cognitive learning outcomes of students, especially on ionic equilibrium material in salt solution. This study aims to improve students' cognitive chemistry learning outcomes on ion equilibrium in salt solution by applying the jigsaw-type cooperative learning model. This research is a classroom action research with the Kemmis and MC models. Taggart, which included the stages of planning, implementing, observing / collecting data and reflecting, which were carried out in 2 (two) cycles. This research was conducted in class XI IPA at public high school Christian YABT Manokwari with a sample of 17 students. The data collection techniques used were tests and observation sheets. The results showed that the increase in the average value of learning outcomes chemistry from cycle I was 56.18 with classical completeness of 29% to 85.29 with classical completeness of 82% in cycle II. The results of observations on learning using the jigsaw type cooperative model have good responses from students. This proves that the type of jigsaw cooperative learning has a positive impact on students in the teaching and learning process. Keywords : Jigsaw Model, learning outcomes cognitive, Ion Balance,  Salt Solution